Analisis Metodologi dan Materi Buku Bahasa Indonesia bagi Penutur Asing - Siti Amaliyah; Dendy Sugono; Restoeningroem Restoeningroem (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2022)
This study is to analyse the methode and material of Bahasa Indonesia Business Comunication for foreigner textbook level 1 students published by UMN Press 2019. This study uses qualitative describtive approach. The data source used is the BIPA Comunication Business textbook for BIPA level 1 students. This research focuses on the feasibility of method and content aspect. The instrument used is in the form of an analysis sheet of the textbook feasibility assessment theory based on Hartono (2016) which analyse in each unit on. Based on the research results, it can be concluded that the BIPA Business textbook level 1 students is “quite feasible” to use, with an eligibility percentage of 90 %. Most of the shortcomings of the textbook are caused by the lack of links and references as well as the incompatibility of the material and vocabulary with the learning targets and elements of BIPA Comunication Business level 1 competence. Keywords: Methode; Material; Bahasa Indonesia for foreigner.